Intravenous aminophylline treatment for severe asthma exacerbation in a toddler: an evidence-based case report - Merrynta Rahmania; Ery Olivianto (Pediatric Sciences Journal, 2022)
Introduction: Asthma is the most prevalent chronic condition in childhood causing enormous morbidity and mortality worldwide. Acute severe exacerbations are potentially life-threatening and often need hospitalization. Incomplete or poor response to initial treatment requires additional interventions that commonly are intravenous second-line drugs, of which Aminophylline is one of them. Although Aminophylline is costly and effective, views are polarising that its use is unsafe. Herein we report a case of intravenous aminophylline use in severe asthma exacerbation in a toddler. Case description: A 3-year-old boy previously diagnosed with asthma came to the emergency room due to severe shortness of breath. He had breathlessness which was more pronounced when he was lying down. He looked restless and irritable. Bilateral wheezing, tachypnea, tachycardia and chest withdrawal were noted. Because of poor response to standard initial treatment, intravenous Aminophylline was given and showed complete relief without the occurrence of the anticipated serious adverse event. Conclusion: When first-line inhaled/nebulized medication fails to control a child's asthma exacerbation, Aminophylline may be utilized. It must be considered a cost-effective treatment for acute asthma exacerbations, especially for developing countries with limited health budgets, even though it is thought to have a narrow therapeutic range and a large inter-individual variance in clearance.